CLINICAL ANALYSIS OF EFFICACY OF ELECTROCONVULSIVE THERAPY WITH MODERN ANESTHETIC SUPPORT IN PSYCHIATRIC PRACTICE - I. V. DUBATOVA; S. A. SOLOV'EVA; I. N. KUCHERENKO; N. V. NIKONOVA; I. V. STOJAKIN; K. A. KARNAUH; O. A. TREPKO; A. V. SAFRONENKO (Кубанский научный медицинский вестник)
Aim. Clinical analysis of the efficacy of electroconvulsive therapy (ECT) in conditions of intensive care units (ICU) in psychiatric dispensary. Materials and methods. Within the two years of ICU functioning 150 patients (73 men and 77 women) aged 17 to 66 were treated with ECT in the Aksai branch of the "Psychoneurological Dispensary". For the course of therapy, the number of ECT sessions was from 2 to 24. The sessions were conducted both daily and at a frequency of 1-3 times a week, depending on the nosology. To assess the efficacy of ECT, a clinical global impression scale (CGI-I) was used. Results. A significant improvement in the state (1-2 on the CGI-I scale) after ECT sessions was observed in 108 patients (72%), slight improvement in 30 patients (20%), absence of changes in 9 patients (6%) and deterioration in 3 patients (2 %). High clinical efficacy of ECT prevailed in the spectrum of patient changes in the clinical group. Regardless the leading syndrome, a significant improvement in the state after the use of ECT prevailed in frequency. Taking into account the diagnostic category and the syndrome, the best effect was observed in the catatonic-oneiroid syndrome in paroxysmal (recurrent) schizophrenia, malignant neuroleptic syndrome, affective-delusional syndrome in schizoaffective disorder, catatonic paranoid and paranoid syndromes within the paranoid schizophrenia with episodic-progressive type of course with an increasing defect, as well as in paranoid schizophrenia with a follow-up period of up to 1 year. ECT was effective in overcoming psychopharmacotherapeutic resistance. Conclusion. Use of ECT in the "modified" version is a highly effective method of biological therapy, providing therapeutic results in catatonic paroxysmal (recurrent) schizophrenia, schizoaffective disorder, paranoid paroxysmal schizophrenia, paranoid schizophrenia with a follow-up period of up to 1 year, as well as in the treatment of malignant neuroleptic syndrome and psychopharmacotherapy resistant conditions.